2007
DOI: 10.1590/s0104-12902007000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de parasitos intestinais e aspectos socioambientais em comunidade indígena no Distrito de Iauaretê, Município de São Gabriel da Cachoeira (AM), Brasil

Abstract: Situado em Terra Indígena do Alto Rio Negro, Iauaretê é o segundo maior pólo de concentração humana no município de São Gabriel da Cachoeira (AM) e agrega dez vilas, com 15 etnias. Esse distrito indígena vem sofrendo processo de transformação progressiva de padrão de ocupação disperso e ribeirinho para núcleo com feições urbanas, com aproximadamente 2700 habitantes, desencadeando problemas de saúde pública. Com objetivo de investigar a distribuição de prevalências de parasitos intestinais na população local e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
3
23

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 13 publications
5
11
3
23
Order By: Relevance
“…The high overall prevalence of infections with helminth and intestinal protozoa observed in our study corroborates previous studies from the micro-region of the Negro River in the State of Amazonas, which reported prevalence between 69.3% and 87.6% (3) (4) (11) . In these studies, A. lumbricoides was almost always the most prevalent in comparison with other intestinal pathogenic parasites, with the prevalence ranging from 19.3% in the municipality of São Gabriel da Cachoeira (Iauaretê) to 51% in the City of Barcelos (3) (12) .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The high overall prevalence of infections with helminth and intestinal protozoa observed in our study corroborates previous studies from the micro-region of the Negro River in the State of Amazonas, which reported prevalence between 69.3% and 87.6% (3) (4) (11) . In these studies, A. lumbricoides was almost always the most prevalent in comparison with other intestinal pathogenic parasites, with the prevalence ranging from 19.3% in the municipality of São Gabriel da Cachoeira (Iauaretê) to 51% in the City of Barcelos (3) (12) .…”
supporting
confidence: 91%
“…In these studies, A. lumbricoides was almost always the most prevalent in comparison with other intestinal pathogenic parasites, with the prevalence ranging from 19.3% in the municipality of São Gabriel da Cachoeira (Iauaretê) to 51% in the City of Barcelos (3) (12) . The E. histolytica complex was the next in most frequent, with prevalence of 7.3% to 34% (11) (13) . The prevalence of other helminths, such as S. stercoralis, hookworm, and T. trichiura also varied in several studies.…”
mentioning
confidence: 99%
“…Another strategy that was used in this training experience was the involvement of the course participants in the performance of interviews at the households of the main village of the District of Iauaretê, with the objective of identifying possible changes in the local socio-environmental, health and sanitation conditions after the action research process began in 2005 (Giatti et al, 2007;Rios et al, 2007). The interview form was constituted of eight questions of qualitative and quantitative nature, three about water sources and domestic uses, three about human waste disposal and two about the final waste disposal.…”
Section: Interviews About the Sanitation Situationmentioning
confidence: 99%
“…Others changed it due to the demand of the municipal government. Analyzing comparatively and qualitatively data from these interviews with results obtained from a situational diagnosis that was carried out in 2005 (Giatti et al, 2007;Rios et al, 2007), at the beginning of the project, even though through distinct methodologies, the importance given to the use of rainwater for human consumption stood out in this new stage. The inhabitants consider that the quality of rainwater is better than that of the other sources.…”
Section: Interviews About the Sanitation Situationmentioning
confidence: 99%
See 1 more Smart Citation